2016
DOI: 10.1016/j.ajodo.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval analysis of lingual fixed retainer adhesives

Abstract: INTRODUCTION:Our objective was to analyze the surface and bulk properties alterations of clinically aged composites used for fixed retention. METHODS: Twenty-six lingual retainers bonded for different time periods (2.2-17.4 years) were retrieved from postorthodontic patients. Fifteen lingual retainers had been cemented by a chemically cured adhesive (Maximum Cure, Reliance Orthodontic Products, Itasca, Ill), and 11 were treated with a photo-cured adhesive (Flow-Tain, Reliance Orthodontic Products). The first g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The results for GA are similar to the data provided by the manufacturer (7.9 GPa) [24] and a previous study after testing in three point bending [19]. The moduli of FT and TL were also found close to previously reported values (FT 5.2 GPa [13]), (TL 17.3 GPa [6,25]) after IIT. The same is true for E IT for TX (15.0 GPa [6]), a value close to one provided by the manufacturer (16.4 GPa [23]) and the value of 14.3 GPa calculated after three point bending [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results for GA are similar to the data provided by the manufacturer (7.9 GPa) [24] and a previous study after testing in three point bending [19]. The moduli of FT and TL were also found close to previously reported values (FT 5.2 GPa [13]), (TL 17.3 GPa [6,25]) after IIT. The same is true for E IT for TX (15.0 GPa [6]), a value close to one provided by the manufacturer (16.4 GPa [23]) and the value of 14.3 GPa calculated after three point bending [16].…”
Section: Discussionsupporting
confidence: 90%
“…A small value indicates a ductile material while a high value indicates a brittle one. The results of this study are close to previously reported values for LR (33.6%) [ 6 , 25 ], TX (30.7%) [ 6 ]), and FT (45.0%) [ 13 ], while to the best of our knowledge there are no comparable data available on the creep resistance of orthodontic adhesive apart from one recently published study where only one commercially available product was tested [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies have analyzed the retention phase in terms of: stability, retention material, adhesion, clinicians and patients’ preference, and hygiene. Researchers have described the best characteristics for adhesion systems in fixed retainers, considering mechanical properties of the composite and wear resistance [ 2 , 3 ], while other authors focused on long-term stability of the tooth position [ 4 ] and periodontal health in comparison with control groups or removable retentions [ 5 , 6 ], but there is a lack of literature focused on the study of the consequences of retention in the enamel.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, retention is considered the final and essential step to maintain, through an adequate appliance, the correct position reached by dental elements at the end of the active orthodontic therapy. Clinicians agree that retention should be maintained as long as a perfect alignment is desired [2]. Several studies investigated the most used retention device in various European and non-European countries, and bonded retainers resulted to be the most widely used device in different countries, especially for the mandibular arch [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%